Stromal modifying CHST15 siRNA enhances antitumor effect synergistically with anti-PD-1 immune checkpoint antibody in murine pancreatic cancer - Juanjuan Ye; Futoshi Suizu; Keiko Yamakawa; Hiroyuki Yoneyama; Jiro Kondo; Motohiko Kato; Akira Nishiyama; Naohisa Yahagi; Kyuichi Kadota (Scientific Reports)
Abstract Tumor stromal remodeling is an obstacle for immune checkpoint inhibitors (ICI). A stroma modifying small interfering RNA (siRNA) to carbohydrate sulfotransferase 15 (CHST15) was recently shown to enhance tumor-infiltrating T cells, yet its impact on antitumor response of ICI remains unexplored. In mouse pancreatic cancer KPC and Pan02 subcutaneous syngeneic tumor models, mice were divided into 4 groups for treatment; (1) control, (2) CHST15 siRNA monotherapy, (3) anti-programmed death receptor 1 (PD-1) monotherapy, and (4) combination therapy with CHST15 siRNA and anti-PD-1 antibody. Mice were sacrificed after 2 week-treatments and anti-tumor effects were evaluated by immunohistochemistry for KPC and flow cytometry for Pan02 model, respectively. In the KPC model, combination treatment with intratumoral CHST15 siRNA (0.9–1.0 mg/kg) and systemic anti-PD-1 antibody (5 mg/kg) synergistically and robustly suppressed tumor growth with a significant increase of tumor-infiltrating CD4+ and CD8+ T cells compared to anti-PD-1 monotherapy. In the Pan02 model, combination treatment with CHST15 siRNA and anti-PD-1 showed anti-tumor effect with significant increases in % necrosis area of the tumor, and tumor-infiltrating T cells compared to the control. Notably, the combination therapy dramatically diminishes Ly6C+Ly6G+ granulocytic myeloid-derived suppressor cells (MDSCs) compared to anti-PD-1 monotherapy. The present study demonstrated the robust synergy between systemic anti-PD-1 antibody and a single stroma modifying agent. Combination usage of intratumoral CHST15 siRNA would provide a novel therapeutic option to trigger the remarkable effect of ICI on this most hard-to-treat solid tumor.